O papel da dicer na diferenciação de adipócitos marrons in vivo - Branquinho, Jessica Lais de Oliveira [UNIFESP] (2017)
Objective: To generate dicer knockout mice in mesenchymal precursor cells expressing myogenic factor 5 (Myf5) and to evaluate the in brown adipose tissue function in mice. Methods:In addition to generating the constitutive knockout mice, we generated the tamoxifen inducible knockout model at different stages of the mouse development. In addition, we performed several experiments to evaluate the metabolic profile, tissue distribution and thermogenic function of brown adipose tissue.Results: Because Dicer knockout in Myf5 + precursor cells was shown to be lethal, the inducible model turned out to be the most suitable model to be studied. Tamoxifen injection in pregnant females proved to be harmful, leading to abortion, but with cesarean surgery it was possible to avoid that. Male mice that were injected with tamoxifen from the newborn stage (seven days of life) showed a strong tendency to exhibit some type of metabolic syndrome, such as insulin resistance, and increased subcutaneous adipose tissue mass. On the other hand, animals treated with tamoxifen before puberty (four weeks of life) showed no differences or trends in all parameters analyzed, regardless of whether male or female. However, knocking out Dicer in the adult period (three months of life) resulted in significant differences in thermogenesis and tissue distribution. Dicer knockout males showed a significant decrease in thermogenic function of brown adipose tissue when exposed to cold and females were able to maintain a higher temperature during chronic cold exposure, in addition to showing a decrease in the gastrocnemius muscle mass after cold. Both genders showed a significant increase in brown adipose tissue, liver and kidney mass after a period of chronic cold exposure, independent of the genotype. In addition, it was possible to verify changes in the histological pattern of adipose tissues in the knockout animals, whereas different in males and females. Conclusions: The lethality of the constitutive knockout model may be due to the fact that Dicer and microRNAs are very important for the development of cells, but the reasons that lead to non-viability are not clear. The inducible knockout model was shown to be effective in this study and differences in the knockout effects were found at different stages of animal development depending on the degree of tissue formation, the methodology of brown adipose tissue activation and the gender. This study may help the understanding of the development and formation of adipose xx tissue and the metabolic effects that lack of Dicer in mesenchymal precursor cells expressing Myf5 may cause. cause.